Management Education: An Interdisciplinary Problem Solving Approach - Johnson, Thomas E.; Werner, David (Academy of Management Journal, 1975)
The Management Problem Laboratory is an interdisciplinary program for the development of managerial problem solving skills. Students investigate current problems of organizations through interaction with an extensive data base and view the problems from the perspectives of several courses in which they are simultaneously enrolled. Data on changes produced are presented.